Analysis of the hemostatic potential of modern topical sealants on arterial and venous anastomoses: an experimental porcine study - Fonouni, Hamidreza; Kashfi, Arash; Majlesara, Ali; Konstantinidis, Lukas; Kraus, Thomas W.; Mehrabi, Arianeb; Oweira, Hani (Journal of materials science, 2017)
One of the widely accepted adjunctive agents in the variety of surgical modalities are sealants. Our study aim was to compare four commonly used modern sealants in a standardized experimental setting to assess their feasibility, and hemostatic efficacy in vascular anastomosis. Forty landrace pigs (weight: 24.7 ± 3.8 kg) were randomized into the control (n = 8) and four sealant groups; TachoSil® (n = 8), Tissucol Duo® (n = 8), Coseal® (n = 8), and FloSeal® (n = 8). After doing a portal vein end-to-end anastomosis as well as stitches of aortic incision, the sealants were applied on anastomotic site. The control group was left intact. In portal vein anastomosis, the sealants led to a complete hemostasis significantly better than control group. The mean of blood loss was also significantly reduced. In successful subgroups, there was a difference in the mean-time to reach complete hemostasis ranging from 15 s in Coseal® to 76 s in FloSeal® group (p < 0.05). In aortotomy experiments, except Tissucol Due®, which had insufficient hemostasis, other sealants led to a complete hemostasis. The mean blood loss was significantly reduced in sealants groups as well. The four sealants are effective in reducing the suture-hole bleeding in portal vein anastomosis. However, the hemostatic potential is heterogeneous among sealants. This means that “one-size-fits-all” approach is not appropriate for application of sealants in diversity of vascular surgery and it should be based on the type and the severity of injury and the structure of tissue.Graphical abstractComparison of hemostasis efficacy of four modern sealants (TachoSil®, Tissucol Duo®, Coseal®, and FloSeal®) in vascular anastomosis in porcine model. The figures below show the total blood loss (g) in the control and sealant groups after aortotomy (left) and portal vein anastomosis (right). The mean of blood loss decreased significantly by the usage of sealants in both experiment groups as compared to control group (*: p < 0.05; sealant groups vs. control group).1. The right column shows the mean of blood loss (g) in all experiments in each group.2. The middle column presents the subgroup with unsuccessful hemostasis at the end of observation time (Tmax = 20 sec. for aortotmy and 300 sec. for portal vein anastomosis).3. The left column shows mean of total blood loss in subgroups with successful hemostasis during observation time (20 sec for aortotomy and 300 sec for portal vein). Open image in new window